Southern Europe and the Frugal Four: Pathological external indebtedness? - Andrea Carrera; Luís Cárdenas; Víctor Arribas Martínez (PSL Quarterly Review, 2025)
This research uses linear correlation and time-series analysis to examine the evolution of the external debt accumulated in periods of current account deficits and reserve purchases. Statistical data of GIPS countries (Greece, Italy, Portugal and Spain), Ireland, and the United States show that a significant portion of the external debt cannot be explained by balance-of-payment (BoP) analysis. Similarly, the study finds that the external debt of the “Frugal Four” countries (Austria, Denmark, The Netherlands and Sweden) is also higher than explainable through BoP data. The research suggests that, due to the very structure of the international payment system, a country’s over-indebtedness is chronic in nature rather than due to behavioural or cultural factors. To tackle the issue, the development of international central banking is thus suggested.